Factors Influencing Discharge Turnaround Time in Avenue Hospitals, Kenya - Mutia, Yvonne; Kawila, Carol; Muiruri, Lillian (International Journal of Health Sciences, 2025)
Purpose: This study evaluated Avenue Hospitals’ discharge process, identified key factors that impact discharge turnaround time (TAT), and offered evidence-based recommendations for improving the entire procedure. The main study objective was to determine the factors that influence discharge turnaround time in three Avenue Hospitals based in Thika, Kisumu, and Parklands. Methodology: This research utilized quantitative approach, which covers the plan for collecting, measuring, and analyzing the data. The study deployed stratified random sampling to select participants from the target population. The sample size was 210 participants. Self-administered Google Forms questionnaire and discharge TAT time logs were used as sources of data. Descriptive analysis, linear regression, time series analysis, and control run charts were conducted and the results were presented in tables and graphs. Findings: Factors that significantly impacted discharge process include delayed completion of discharge paperwork, billing errors, discharge planning with reconciliation of medications, poor communication among healthcare workers, and availability of dedicated billing personnel (p<0.01). In the lean six-sigma (LSS) analysis, the discharge process is generally not in control. The pediatrics and medical-surgical units have higher variability than maternity and psychiatry in the discharge TAT Unique contribution to theory, practice, and policy: This study provides empirical evidence on the utility of LSS and DMAIC (Define, Measure, Analyze, Improve, and Control) models in identifying discharge bottlenecks and implementing quality improvements in hospital systems. It also emphasizes the need for institutional reforms, such as streaming staffing and discharge planning protocols to enhance patient flow and satisfaction.